Comparison of five tests used in diagnosis of neonatal bacteraemia. Issue 6 (June 1988) - Kite, P; Millar, M R; Gorham, P; Congdon, P
Abstract : The neutrophil count, immature:total neutrophil ratio, C reactive protein assay, nitroblue tetrazolium test and an acridine orange leucocyte cytospin test were evaluated for the diagnosis of neonatal bacteraemia. The acridine orange leucocyte cytospin test gave the highest specificity and positive predictive accuracy, but was less sensitive than the neutrophil count, C reactive protein assay or nitroblue tetrazolium test, particularly for the diagnosis of bacteraemia caused by coagulase negative staphylococci. No single test gave the sensitivity, specificity, and positive predictive accuracy of the combined results of the acridine orange leucocyte cytospin, C reactive protein, and nitroblue tetrazolium tests.